Dampak Perceraian Orang Tua terhadap Akhlak Remaja - Elsa Nurul Khadijah (UIN Sunan Gunung Djati Bandung, 2023)
This study aims to discuss the impact of parental divorce on adolescent morals. This study uses a qualitative approach by applying a descriptive-analytical method. The formal object of this research is the theory of divorce, while the material object is the reality of adolescent morality. The results and discussion in the study show that there are several bad morals (akhlaqul mazmumah) caused by divorce such as being easily angered (ghadab), frustrated (al-Qunuth), and 'Uquuqul walidain' things due to the loss of an authority figure from a father who made him not so afraid anymore of her mother figure which is usually based on disappointment and anger especially when she is considered different by having the status of a divorced child. This study concludes that the divorce of parents has an impact on the emotional, social, or psychological aspects of adolescents so that it has implications for the morals or behaviour they display. This study recommends Islamic institutions and organisations to carry out developments related to the importance of moral development in adolescents impacting divorce, including the way parents behave before, during and after divorce.